ATIVIDADE ANTIOXIDANTE E TEORES DE FENÓIS, FLAVONOIDES E TANINOS TOTAIS DE Nectandra megapotamica (SPRENG.) MEZ. (LAURACEAE) - DAMIÃO, Pamela Deniz; GOMES, Paula Fernanda; SILVA, Ana Francisca Gomes (ANAIS DO ENIC, 2023)
-